Fabrication and Applications of Amperometric Glucose Biosensor Based on CuO Nanowires/Graphene Modified Electrode - Tian1, Liangliang; Su1, Yongyao; Liao2, Wenli (Asian Journal of Chemistry, 2013)
The copper(II) oxide nanowires (CuO NWs) synthesized by a simple method were applied to construct glucose amperometric biosensor. Graphene was also added to improve the performance of the sensor. The morphology and structure of CuO nanowires were investigated by SEM, TEM and XRD. The electrocatalytic oxidation of the CuO nanowires/graphene modified electrode towards glucose was studied by cyclic voltammetry and chronoamperometry. It is notable that the determination of the glucose has been achieved in enzyme-free conditions. The modified electrode presented excellent stability, reproducibility, high selectivity and quick response. The developed nonenzymatic biosensor exhibited excellent electroactivity towards glucose over a wide linear range of 1.6 μM-6.0 mM with a sensitivity of 375 μA cm-2 mM-1.